2022
DOI: 10.1038/s41467-022-29498-9
|View full text |Cite
|
Sign up to set email alerts
|

ESR1 mutant breast cancers show elevated basal cytokeratins and immune activation

Abstract: Estrogen receptor alpha (ER/ESR1) is frequently mutated in endocrine resistant ER-positive (ER+) breast cancer and linked to ligand-independent growth and metastasis. Despite the distinct clinical features of ESR1 mutations, their role in intrinsic subtype switching remains largely unknown. Here we find that ESR1 mutant cells and clinical samples show a significant enrichment of basal subtype markers, and six basal cytokeratins (BCKs) are the most enriched genes. Induction of BCKs is independent of ER binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 123 publications
1
20
0
1
Order By: Relevance
“…S11A). Surprisingly, mining our MCF7 ESR1 mutant cell model ER ChIP-seq data (46) showed an absence of proximate Y537S or D538G mutant ER binding sites (± 50kb of TSS) at desmosome and connexon target gene loci. These results suggest that the We therefore hypothesized that these altered adhesion target genes might be regulated via a secondary downstream effect of the hyperactive mutant ER.…”
Section: Mutant Esr1 Cells Show Increased Desmosome Gene and Gap Junc...mentioning
confidence: 79%
“…S11A). Surprisingly, mining our MCF7 ESR1 mutant cell model ER ChIP-seq data (46) showed an absence of proximate Y537S or D538G mutant ER binding sites (± 50kb of TSS) at desmosome and connexon target gene loci. These results suggest that the We therefore hypothesized that these altered adhesion target genes might be regulated via a secondary downstream effect of the hyperactive mutant ER.…”
Section: Mutant Esr1 Cells Show Increased Desmosome Gene and Gap Junc...mentioning
confidence: 79%
“…Research linking ESR1 mutations and immune activation remains scarce. We reported previously that ESR1 mutant metastatic samples have higher levels of macrophages, and also proposed possible mechanisms including activation of innate immune response via STING pathways and production of CHI3L1 enhanced recruitment of macrophages via elevated S100A8/A9-TLR4 signaling 23 , 83 . Here we identified a further significantly increased level of total and PD-L1 positive macrophages in the rare tumors with co-occurring TP53 - ESR1 mutations.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown immune modulation in both TP53 and ESR1 mutant tumors 23 , 83 85 . First, it has been reported that specific p53 mutant variants such as R175H are associated with elevated macrophage recruitment 86 , 87 .…”
Section: Discussionmentioning
confidence: 95%
“…Промоторы активных генов совпадают с областями открытого хроматина и демонстрируют характерный паттерн распределения нуклеосом [64] DNase-seq [65] MNase-seq [66] ATAC-seq [67] FAIRE-seq [68] Пространственная организация хромосом Энхансеры [69] и сайленсеры [54,61,70] физически взаимодействуют с промоторами при помощи петлевых контактов. Инсуляторы формируют петлевые домены, ограничивающие область действия энхансеров [71,72] HiC [73] ChIA-PET [74] HiChIP [75] PLAC-ChIP [76] www.clinpractice.ru химерного белка подавляется, а клетки, содержащие такую конструкцию, сохраняют жизнеспособность при химической индукции апоптоза. Таким образом, в пуле трансфицированных клеток выживают только несущие генетические конструкции, содержащие сайленсеры.…”
Section: массовый параллельный репортерный анализ для исследования ци...unclassified